2010
DOI: 10.1007/s10803-010-0941-y
|View full text |Cite
|
Sign up to set email alerts
|

Play and Developmental Outcomes in Infant Siblings of Children with Autism

Abstract: We observed infant siblings of children with autism later diagnosed with ASD (ASD siblings; n = 17), infant siblings of children with autism with and without other delays (Other Delays and No Delays siblings; n = 12 and n = 19, respectively) and typically developing controls (TD controls; n = 19) during a free-play task at 18 months of age. Functional, symbolic, and repeated play actions were coded. ASD siblings showed fewer functional and more non-functional repeated play behaviors than TD controls. Other Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 42 publications
7
50
1
2
Order By: Relevance
“…It may be that differences in types of play and other behaviors may not be clear until after age 12 mo. Christensen et al (2010), for example, in a study of infant siblings of children with ASD at age 14 mo, found that high-risk infants engaged less often in functional play than did age-matched, typically developing counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that differences in types of play and other behaviors may not be clear until after age 12 mo. Christensen et al (2010), for example, in a study of infant siblings of children with ASD at age 14 mo, found that high-risk infants engaged less often in functional play than did age-matched, typically developing counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a modest number of studies have suggested that the relatives of autistic probands display a milder version of these clinical manifestations. In a study on infant siblings of children with autism, Christensen et al (2010) reported significantly higher frequency of nonfunctional repeated play behaviours compared to typically developing infants. In a study involving older relatives, Smith et al (2009) carried out a factor analysis on the restricted, repetitive behaviours and interests (RRBI) domain of autism using the Autism Diagnostic InterviewRevised and examined associations between RRBI and personality traits linked to autism in the parents.…”
Section: Repetitive Stereotyped Behaviour and Interestsmentioning
confidence: 95%
“…Other studies looking at the early social BAP include Toth et al (2007) and Christensen et al (2010) who examined play behaviour in at-risk siblings. Using the Communication and Symbolic Behavior Scale-Developmental Profile (Wetherby and Prizant 2002), Toth et al reported that infant siblings of children with autism displayed less symbolic behaviour as well as fewer responsive social smiles and distal gestures such as pointing during social interactions.…”
Section: Reciprocal Social Interactionmentioning
confidence: 99%
“…As far as retrospective studies are concerned, several works focused on the analysis of movement and sensory-motor development Damiano et al, 2013;Flanagan et al, 2012;LeBarton and Iverson, 2013;Loh et al, 2007;Mulligan and White, 2012;Nickel et al, 2013), on the analysis of social behaviors (Christensen et al, 2010;Cornew et al, 2012;Landa et al, 2007;Nadig et al, 2007;Ozonoff et al, 2010;Presmanes et al, 2007;Sullivan et al, 2007), and on the precursors of communication such as crying or vocalizations (Paul et al, 2011;Sheinkopf et al, 2012). Other studies analyzed parent-infant interaction, during the face to face-still face paradigm (Cassel et al, 2007;Chow et al, 2010;Hutman et al, 2012;Ibanez et al, 2013;Rozga et al, 2011;Yirmiya et al, 2006) or during unstructured play sessions.…”
Section: Baby Siblings Researchmentioning
confidence: 99%